Simulation research on the blister evolution behaviors of UMo/Zr monolithic fuel elements - Changbing, Tang; Feng, Yan; Yongjun, Jiao; Yong, Xin; Zengping, Pu; Zhong, Xiao (Frontiers in Energy Research, 2024)
Blister behavior is one of the main failure modes of UMo/Zr monolithic fuel elements during irradiation. The temperature of fuel elements may increase greatly so that the fuel elements may be destroyed. Post-irradiation annealing tests are used to study the blister behaviors of fuel elements under high temperature. In this study, a simulation method is developed based on the finite element method to study the evolution of blister behaviors of UMo/Zr monolithic fuel elements in the blister tests, taken into considering that the evolution of bubble pressure should be coupled with the deformation of cladding. The influence of creep rate of the cladding on the evolution of blister height is analyzed. The study shows that the unrecoverable creep deformation of the cladding, which occurs under high temperature, is the major factor in the increment of bubble height. The increase of bubble height mainly occurs during the heat preservation process and the initial stage of cooling process. The creep rate of cladding is positively related to the evolution of bubble height.